Performance and Cost-effectiveness of Pooling COVID-19 Samples Using Real time Polymerase Chain Reaction Test - Shrestha, Ira; Maharjan, Shreekrishna; Bhandary, Shital; Prajapati, Sunita; Chaurasiya, Ajay; Bakhunchhe, Rojina (Journal of Nepal Health Research Council, 2022)
Background: Rapid detection of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) by real-time polymerase chain reaction (RT-PCR) is the most reliable method used worldwide. Although the incidence of the disease has increased globally, the limited availability of PCR kits has become the major bottleneck for the diagnosis of COVID positive patients.Methods: Random samples were pooled for two months in group of two-five and tested for SARS-CoV-2. If the pool was negative, all individuals in the pool were reported negative. If the pool was positive, then the individual samples were retested to identify the positive individual.Results: The mean cycle threshold (Ct) value of pooled samples was not significantly different with that of individual samples for N, ORF-1ab and E genes. Also, pooling saved more than 60% of reagents, time and effort, workforce and cost.Conclusions: In this study, the positivity rate was around 5% and saving of reagent, cost, time and manpower was more than 60%.Keywords: RT-PCR; Sample Pooling; SARS-CoV-2